2017
DOI: 10.1111/fcsr.12228
|View full text |Cite
|
Sign up to set email alerts
|

A Qualitative Evaluation of a Fitness and Nutrition‐Focused Wellness Program

Abstract: Nutrition education interventions have shown some effectiveness at promoting healthy diets. However, qualitative investigations might enhance understanding of factors that facilitate behavior change. The purpose of this study was to explore factors that facilitate behavior change among participants of a nutrition intervention for underserved citizens in Southern California. A focus group with eight participants suggested themes that included changes in nutrition knowledge, attitudes, and skills; successful pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(15 citation statements)
references
References 20 publications
0
15
0
Order By: Relevance
“…How valuable is the research? * Andrews et al ( 2017 ) Yes Yes Yes Yes Yes No No Yes Yes High Edward and Evers ( 2001 ) Yes Yes Yes Yes Yes No Yes No Yes Moderate Hu et al ( 2013 ) Yes Yes Yes Yes Yes Yes Yes Yes Yes High Knapp et al ( 2019 ) Yes Yes Yes Yes Yes No Yes Yes Yes Moderate McFadden et al ( 2014 ) Yes Yes Yes Yes Yes Yes Yes Yes Yes High Ohly et al ( 2019 ) Yes Yes Yes Yes ...…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…How valuable is the research? * Andrews et al ( 2017 ) Yes Yes Yes Yes Yes No No Yes Yes High Edward and Evers ( 2001 ) Yes Yes Yes Yes Yes No Yes No Yes Moderate Hu et al ( 2013 ) Yes Yes Yes Yes Yes Yes Yes Yes Yes High Knapp et al ( 2019 ) Yes Yes Yes Yes Yes No Yes Yes Yes Moderate McFadden et al ( 2014 ) Yes Yes Yes Yes Yes Yes Yes Yes Yes High Ohly et al ( 2019 ) Yes Yes Yes Yes ...…”
Section: Resultsmentioning
confidence: 99%
“…All studies reported outcomes for participants, including developing nutrition knowledge and skills (e.g., reading nutrition labels, planning meals, cooking skills) (Andrews et al, 2017 ; Edward & Evers, 2001 ; Knapp et al, 2019 ; Pettigrew et al, 2017 ); increased quality of diet (e.g., increased consumption of fruits and vegetables, reduced consumption of fast food) (McFadden et al, 2014 ; Ohly et al, 2019 ; Palar et al, 2019 ; Savoie Roskos et al, 2017 ; Saxe-Custack et al, 2018 ); hunger alleviation and increased food security (Edward & Evers, 2001 ; Saxe-Custack et al, 2018 ); and development of social support networks (Edward & Evers, 2001 ; Knapp et al, 2019 ; Pettigrew et al, 2017 ; Savoie Roskos et al, 2017 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In Cohort 1, a qualitative design was used to collect formative evaluation data to assess fit between the program and the audience and to guide future modifications of the program. Qualitative methods are useful for gaining insight into how and why specific program elements operate well or need adjustment, and have been used in similar studies (Andrews, Gray, Galvan, & Donlin, 2017; Besnilian, Johnson, & Plunkett, 2018). Following each lesson, parent participants completed a survey with three open‐ended questions assessing what they liked about the lesson, what they found helpful, and suggestions for improvement.…”
Section: Methodsmentioning
confidence: 99%